A Random Number Generator Experiment: The Origin of Decision Augmentation Theory. - May, Edwin C. (Journal of Parapsychology)
In 1979, the research team at SRI International conducted a single random number generator (RNG) experiment. The goal was to replicate and extend the findings from a substantial literature in several ways. Sequential analysis was used to provide a two-fold increase in statistical sensitivity; two fundamentally different physical random sources were used: β-decay of 147Pm and electronic noise from a well-understood silicon noise diode. Substantial engineering effort isolated these sources from environmental effects, and a quantum mechanical model accurately described the known properties of the electronic noise diode. An a priori definition of a successful outcome was more stringent than in the usual study; two participants out of seven must produce independently significant evidence of an effect. Seven participants who were screened for PK ability from a population of 17 candidates took part in the formal study. Two produced independently significant results (p ≤ 0.021 and p ≤ 0.039, respectively). While these results were consistent with those in the micro-PK literature, we report definitive evidence of no PK effects at all. Rather, the result appears to arise because of informational psi on part of the participant.